Comparison of Long-Acting Somatostatin Analogue (SMS 201-995) and Balloon Tamponade in Treatment of Acute Vaticeal Hemorrhage - S. KAPICIOĞLU; G. BAYRAM; C. DEMİRCAN; M. K. GÜL; A. FİSKECİ; N. KAYA (Turkish Journal of Gastroenterology, 2020)
-